Propositions for a Resilient, Post-COVID-19 Future for the AEC Industry - Nassereddine, Hala; Seo, Kyung Wook; Rybkowski, Zofia K.; Schranz, Christian; Urban, Harald (Frontiers in Built Environment, 2021)
The coronavirus outbreak has challenged and continues to challenge every aspect of the supply chain within the AEC industry, forcing stakeholders to cope with increasing uncertainties and continuous change. The notion of resilience is especially salient now. While the need for the AEC industry to focus on resilience has been highlighted in recent articles, there is a need for a comprehensive discussion on what resilience means for the AEC industry and how companies can create built-in resilience. This paper takes the form of a high-level overview of where the industry is headed and aims to establish eleven propositions for a resilient, post-COVID-19 future, for practitioners working in the design and construction industry. Moreover, this paper proposes a ‘decentralization of workforce and integration of data’ model in which the established propositions are manifested to support a resilient AEC industry.